Neonatal head circumference (NHC) as an indicator of complicated birth. (18th April 2012) - Burke, N; Walsh, J; Donnelly, JC; Cooley, SM; Geary, M; Breathnach, F; Burke, G; Dicker, P; Tully, E; Daly, S; Morrison, JJ; Higgins, JR; et al.
Abstract : This study assessed if the NHC could be an indicator of complicated birth. Prospectively collated data from two tertiary referral medical centres were amalgamated and analysed for maternal age, body mass index (BMI), biometry, labour and neonatal outcomes. Delivery was considered complicated if achieved by emergency Caesarean section or operative vaginal delivery, while spontaneous vertex delivery was classified as 'uncomplicated'. Data analysis was performed using SAS and SPSS software. A total of 4399 nulliparous singleton term pregnancies were included for analysis. 53.5% (2354) had an "uncomplicated birth". 37cm was identified as the 90th centile for NHC. The odds ratio for having a "complicated birth" if the NHC was greater than the 90 th centile was 2.9 (95% CI 2.1-4.0). This effect remained after adjusting for increasing maternal age (OR 2.6, 95% CI1.3 - 1.8) and increasing BMI (OR 1.3, 95% CI 1.04 -1.8). This large prospective cohort study demonstrates that NHC >90 th centile is associated with an increased incidence of difficult birth. This raises the possibility of correlation of this measurement with determination of fetal head circumference in order to better predict those who may require operative vaginal delivery or indeed avoid attempted vaginal birth in the first place.